Mapping a Decade of Research on Family Enterprises Reinvention - A Bibliometric Analysis - Emy Widyastuti; Muhammad Sholahuddin; Nourelhuda S. B. Elmanaya (Jurnal Manajerial, 2026)
Background – This study analyzes the global evolution of research on family enterprises and reinvention over the past decade using a Scopus-based bibliometric approach. Aim – This study aims to analyze publication trends and scientific productivity in the topic Family Enterprises and Reinvention Globally, identify the authors, journals, and countries that contribute most to the study, classify thematic clusters and develop Conceptual Framework for further research. Design / methodology / approach – Employing PRISMA procedures and Biblioshiny R analysis, 2,690 articles published from 2015–2025 were examined. Findings – Findings reveal that intergenerational innovation capability and organizational identity elasticity are crucial factors for successful business reinvention. Conclusion – This study concludes that research on family enterprises and reinvention has grown significantly, emphasizing that transgenerational innovation capability and organizational identity elasticity are key to enabling family firms to adapt, remain competitive, and sustain long-terma performance in a dynamic and digital business environment Research implication – this study offers insights for family business leaders and policymakers to design sustainable innovation strategies that balance family values and long-term competitiveness. Limitations – This study relies on a limited keyword strategy, which may not fully capture related studies using alternative terms such as family business, family firm, or strategic renewal.